2019
DOI: 10.1080/1369183x.2019.1679413
|View full text |Cite
|
Sign up to set email alerts
|

Intra-EU youth mobility, human capital and career outcomes: the case of young high-skilled Latvians and Romanians in Sweden

Abstract: This article analyses the relationship between human capital and career outcomes using the case of highly skilled young Latvians and Romanians in Sweden. As a non-English-speaking country with regulated labour markets, the Swedish case provides a contrast to previous studies on EU10 to EU15 mobility that usually focus on English-speaking receiving countries with less regulated labour markets. Thirty-eight semi-structured interviews are analysed from a life-course perspective to map the education and career tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…We also suggest that language skills can not only be a prerequisite for effective engagement in employment and career activities (Emilsson & Mozetič, 2019), but may also influence refugees' health and wellbeing. In support of the relationship between language skills and health, previous research has suggested that poor English skills are a common source of depression, stress, and anxiety for migrants living in Australia (Maneze et al, 2014) and that lack of functional local language skills usually hinders refugees from effectively obtaining social and health support (Salami et al, 2019) and identifying feasible ways to integrate socially in host countries.…”
Section: Discussionmentioning
confidence: 91%
“…We also suggest that language skills can not only be a prerequisite for effective engagement in employment and career activities (Emilsson & Mozetič, 2019), but may also influence refugees' health and wellbeing. In support of the relationship between language skills and health, previous research has suggested that poor English skills are a common source of depression, stress, and anxiety for migrants living in Australia (Maneze et al, 2014) and that lack of functional local language skills usually hinders refugees from effectively obtaining social and health support (Salami et al, 2019) and identifying feasible ways to integrate socially in host countries.…”
Section: Discussionmentioning
confidence: 91%
“…These databases provide unique insights into the transferability of human capital in the context of the nine project-partner countries. The papers presented in this Special Issue offer a range of methodological approaches, using qualitative, quantitative or mixed methods; a particular feature is that some papers present a pan-European analysis (Janta et al 2019;McGarry et al 2019), others a two-country comparative analysis (Staniscia et al 2019) or single country cases (Moroşanu et al 2019;Baláž et al 2019;Emilsson and Mozetič 2019;Aksakal and Schmidt 2019), probing deeper into novel questions of human capital. The two studies outside of the YMOBILITY project (Palovic, Janta, and Williams 2019; Grabowska and Jastrzębowska 2019) focus on single country cases; Slovakia and Poland, utilising multiple data sources.…”
Section: Outline Of Papersmentioning
confidence: 99%
“…The focus here is on returnees in different contexts and human capital gains among circular migrants and other mobile groups. Four articles focus on under-studied contexts: examining return migration and its interrelations to location within Southern Europe by comparing returnees' occupational experiences in Italy and Spain (Staniscia et al 2019); exploring trajectories of 'lower-skilled' young migrants in the London region (Moroşanu et al 2019); and examining destination countries with rather highly regulated labour markets, in Sweden (Emilsson and Mozetič 2019) and Germany (Aksakal and Schmidt, 2019). Two articles, both outside of the YMOBILITY project, seek to embed the young migrants' experiences in a broader economic and social canvas: employers, as opposed to the young migrants' perspectives in Slovakia (Palovic, Janta, and Williams 2019) utilising qualitative data; and migration-related skills, both individual and social, contributing to an understanding of the spill-over effects of knowledge transfer after return in Poland (Grabowska and Jastrzębowska 2019) using both quantitative and qualitative data.…”
Section: Outline Of Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…Conterminously, free movement is a core pillar of the EU: It is intended to create a single European labour market and increase its flexibility and efficiency. Moreover, increased mobility is expected to help match labour supply and demand, thus leading to a better utilisation of human capital and thereby increasing economic productivity in line with the Lisbon agenda [1]. Hence, the promotion of mobility has also become a core element of European policy designed to combat youth unemployment.…”
Section: Introductionmentioning
confidence: 99%